Kesiapan Berwirausaha Mahasiswa Teknik Mesin Universitas Muhammadiyah Yogyakarta Ditinjau Dari Pengetahuan Kewirausahaan, Dukungan Keluarga, Soft Skill, Dan Prestasi Belajar - Abang Asriyadi Davinci; Tri Maryati (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2011)
The study aimed to investigate: (1) the influence of entrepreneurship knowledge, family support, soft skill and learning achievement on the students entrepreneurship readiness, (2) the influence of entrepreneurship knowledge on the students entrepreneurship readiness, (3) the influence of family support on the students entrepreneurship readiness, (4) the influence of soft skills on the students entrepreneurship readiness, (5) the influence of learning achievement on the students entrepreneurship readiness. The population of this research was all students of Mechanical Engineering, Faculty of Engineering, Muhammadiyah University Yogyakarta in the academic year of 2011/2012 who had taken the entrepreneurship course. Therefore, the subject of this research was 106 from the academic year of  2006 – 2008.The research finding follow: (1) there are influence of entrepreneurship knowledge, family support, soft skills and learning achievement on the students’ entrepreneurship readiness, (2) there are influence of entrepreneurship knowledge on the students’ entrepreneurship readiness shown by the partial correlations result, (3) there are influence of family support on the students’ entrepreneurship readiness, (4) there are influence of soft skills on the students’ entrepreneurship readiness, (5) there are influence of learning achievement on the students’ entrepreneurship readiness.